KONSEP NEGARA MENURUT PERSPEKTIF AL-MAWARDI - Eka Febriana Putri; Zainuddin Zainuddin (Institut Agama Islam Negeri Batusangkar, 2022)
This paper aims to reveal and explain Al-Mawardi's legal thoughts about the form of the State and the formation of the State. This type of research is library research with a qualitative approach. The technique of collecting materials used is to find and record materials that are relevant to the problem under study. this study finds that, in the concept of Negara al-Mawardi, the position of religion is very important. Al-Mawardi argues that religion and the state need each other so as not to become a secular state. With the state, religion can develop, because the state and religion have a reciprocal relationship. Religion needs the State as a means of preserving religion and developing religion, and vice versa, the State also needs religion, because religion also helps the State in fostering the moral and spiritual ethics of its citizens. On the other hand, the State needs religion, because with religion the State can develop in ethical and moral development. The form of the state according to Al-Mawardi is the caliphate. Al-Mawardi lived in the caliphate government system that was in effect at that time. This can be seen from the appointment of a caliph or imam, the criteria or conditions for becoming a caliph, and the procedure for selecting it. Al-Mawardi argues that the state is formed because of the weakness of the people who cannot meet their own needs, therefore a state is needed. According to Al-Mawardi, the formation of the state must fulfill six points, namely guiding religion as self-control, having an authoritative ruler who will bring change and achieve its goals, justice for oneself and others, universal security in order to achieve good development, and good soil fertility. Sustainability can support the economy, finally the hope of survival, because the progress of a country is also seen through the dimensions of human development. If one of the elements of the formation of the state is not fulfilled then it cannot achieve its objectives.